Foundations of software science and computation structures : 19th International Conference, FOSSACS 2016, held as part of the European Joint Conferences on Theory and Practice of Software, ETAPS 2016, Eindhoven, the Netherlands, April 2-8, 2016, Proceedings /: 19th International Conference, FOSSACS 2016, held as part of the European Joint Conferences on Theory and Practice of Software, ETAPS 2016, Eindhoven, the Netherlands, April 2-8, 2016, Proceedings. (2016) - Unknown
No abstract available